Calibration of thresholds for functional engagement of vagal A, B and C fiber groups in vivo. Issue 1 (January 2018) - McAllen, Robin M; Shafton, Anthony D; Bratton, Bradford O; Trevaks, David; Furness, John B
Vagal nerve stimulation is widely used therapeutically but the fiber groups activated are often unknown.Aim: To establish a simple protocol to define stimulus thresholds for vagal A, B and C fibers.Methods: The intact left or right cervical vagus was stimulated with 0.1 ms pulses in spontaneously breathing anesthetized rats. Heart and respiratory rate responses to vagal stimulation were recorded. The vagus was subsequently cut distally, and mass action potentials to the same stimuli were recorded.Results: Stimulating at either 50 Hz for 2 s or 2 Hz for 10 s at experimentally determined strengths revealed A, B and C fiber thresholds that were related to respiratory and heart rate changes.Conclusion: Our simple protocol discriminates vagal A, B and C fiber thresholds in vivo .